Nantena Alumunium Guna Optimasi Transmisi Gelombang Radio - Roni Kartika Pramuyanti (Sekolah Tinggi Teknik - PLN, 2016)
The Antena is one of instrument from electronic’s communication which very usable to transmit the radio and audio sound wave. There are many basic materials of antenna which can usable, the among others iron, brass, copper, aluminum. All of the basic materials are the materials which can be conductor. From this research, All of the materials to make an antenna has been studied previously can make the optimalization(1) of radio’s wave. The metode to know that is make the antenna with use all of the basic materials. But only one material can be used as be base antenna’s material. That’s alumunium, that’s lightweight and malleable. Some parameters which follow in use of antenna there is on alumunium can be solve, known and found. Among others thing, the shape and surface parameters, impedance, transmit’s power, receive power, and SWR antenna.